Merging black holes: assessing the performance of two analytic gravitational waves models. Issue 3 (2nd March 2023) - Buskirk, Dillon; Babiuc Hamilton, Maria C.
Abstract: Merging black holes produce the loudest signal in the detectors. However, this is the most difficult signal to accurately predict with analytical techniques. Only computer simulations can account for the nonlinear physics during the collision, but they are inherently complex, costly, and affected by numerical errors. In order to bypass this problem, two analytical models for the merger have been developed: the Implicit Rotating Source (IRS) and the newer Backwards one Body (BoB). In this work, we assess the performance of the BoB model by comparing it with the older IRS model and with the numerical data, identifying its strengths and weaknesses. Our main finding reveals discrepancies in amplitude, but overall excellent accord in frequency. The BoB model is comparable with the IRS and NR simulations, having the added advantage that it depends only indirectly on numerical data, it accounts for spin, and it offers a seamless fit with the analytical formalisms for the inspiral. By independently evaluating and testing those models, we bring evidence of their reproducibility, thus upholding high scientific standards, and make available our implementation, enabling readers to evaluate our results themselves.